Tindak Kekerasan yang Melibatkan Anak di Satuan Pendidikan - Ririn Nurfaathirany Heri (CV. ULIL ALBAB CORP, 2024)
Violence in the world of education is increasing both in quantity and quality. This raises questions regarding the quality of education provided to students and teaching staff. As an effort to prevent and handle violence in the educational unit environment, regulations have been made to improve it through the Regulation of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia Number 46 of 2023 concerning Prevention and Handling of Violence in the Education Unit Environment, which regulates the types of violence in the school environment, including violence physical, psychological, bullying, sexual violence, discrimination and intolerance, policies that contain violence and other forms of violence which include students, educators, education staff, parents/guardians, school committees, and communities who have mild, moderate to severe consequences of sanctions .